2019
DOI: 10.17505/jpor.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

Redefining Therapeutic Outcomes of Depression Treatment

Abstract: Responses to evidence-based interventions for depression are divergent: Some patients benefit more than others during treatment and some do not benefit at all or even deteriorate. Tailoring interventions to the individual may improve outcomes. However, such personalization of evidence-based treatment in depression requires investigation of individual outcomes and the individual trajectories towards these outcomes. This theoretical paper provides a critical reflection on individual outcomes of depression treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…What it means for treatment of depression to be successful has been hotly debated, and successful treatment has been conceptualized in many alternative ways (Fava et al, 2007). If treatment success in a predictive study is defined in a way that does not match at all with the experiences of patients or practitioners (see Slofstra et al, 2019), all the predictions will be rendered meaningless and unhelpful for actual practice, no matter how good the predictions are.…”
Section: The Importance Of Conceptual Claritymentioning
confidence: 99%
“…What it means for treatment of depression to be successful has been hotly debated, and successful treatment has been conceptualized in many alternative ways (Fava et al, 2007). If treatment success in a predictive study is defined in a way that does not match at all with the experiences of patients or practitioners (see Slofstra et al, 2019), all the predictions will be rendered meaningless and unhelpful for actual practice, no matter how good the predictions are.…”
Section: The Importance Of Conceptual Claritymentioning
confidence: 99%
“…Considering the impact that depression has on various aspects of patients' lives, there is an additional need to treat patients focusing on core symptom resolution as well as overall and broader well-being, including functional improvement and minimizing residual symptoms [29,[39][40][41][42]. Additionally, it is important to broaden the routine outcome monitoring systems [43] to effectively capture patients' experiences, perspectives, needs, and priorities and incorporating them into the treatment approach for better outcomes [42]. The combination of psychotherapy and pharmacotherapy has already shown to improve QoL and work productivity in patients diagnosed with depression [35,44,45].…”
Section: Study Implicationsmentioning
confidence: 99%
“…As positive affect has been found to be important in the recovery from depression (Geschwind et al, 2011), it is also important to study the effects of MDD interventions on well-being. Additionally, previous studies have found that even when symptoms of depression decrease, patients oftentimes continue to experience impairments in various domains of functioning and quality of life (Slofstra et al, 2019). It is therefore important to also take these types of variables into consideration when evaluating the effectiveness of interventions.…”
Section: Mechanisms Of Mindful Yogamentioning
confidence: 99%